Malaria disrupts the rhesus macaque gut microbiome - Farinella, Danielle N.; Kaur, Sukhpreet; Tran, ViLinh; Cabrera-Mora, Monica; Joyner, Chester J.; Lapp, Stacey A.; Pakala, Suman B.; Nural, Mustafa V.; DeBarry, Jeremy D.; Kissinger, Jessica C.; Jones, Dean P.; Moreno, Alberto; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Previous studies have suggested that a relationship exists between severity and transmissibility of malaria and variations in the gut microbiome, yet only limited information exists on the temporal dynamics of the gut microbial community during a malarial infection. Here, using a rhesus macaque model of relapsing malaria, we investigate how malaria affects the gut microbiome. In this study, 16S sequencing was performed on DNA isolated from rectal swabs of rhesus macaques over the course of an experimental malarial infection with Plasmodium cynomolgi. Members of Proteobacteria (family Helicobacteraceae), increased dramatically in relative abundance in the animal’s gut microbiome during peak infection while Firmicutes (family Lactobacillaceae and Ruminococcaceae), Bacteroidetes (family Prevotellaceae) and Spirochaetes amongst others decreased compared to baseline. Alpha diversity metrics indicated decreased microbiome diversity at the peak of parasitemia, followed by restoration of diversity post-treatment. A comparison with published gut microbiome data from healthy rhesus macaques suggests that the gut microbiome during acute malaria is enriched with mucosa-resident commensal bacteria. We therefore hypothesize that this temporal enrichment in mucosal bacteria on rectal swabs during acute malaria may either be due to sloughing off of the mucosal layer during peak infection and/or selective enrichment of certain microbes as a result of metabolic shifts that occur during disease progression. To explore the latter hypothesis, we performed metabolomics on blood plasma from the animals at the same timepoints and investigated changes in metabolic pathways over time. Significant changes in the tryptophan-kynurenine immunomodulatory pathway were detected at peak infection with P. cynomolgi, a finding that has been described previously in the context of P. vivax infections in humans. During relapses, which have been shown previously to be associated with less inflammation and clinical severity, the gut microbiome was also minimally disrupted, despite parasites being present. Altogether, these data suggest that a joint metabolic and immune shift in the body during peak parasitemia is associated with a concomitant shift in the gut microbiome, which is reversed post-treatment.